Palladium‐Catalyzed [3+2] Cycloadditions of Alkylidenecyclopropanes to Imines: A Direct Approach to Pyrrolidine Scaffolds - Ricardo Rodiño; Felipe Verdugo; José L. Mascareñas; Fernando López (ChemistryEurope)
Abstract Alkylidenecyclopropanes (ACPs) can work as versatile 3 C partners in a range of [3+n] cycloadditions with unsaturated carbon partners. We now demonstrate that they can also be harnessed for inter‐ and intramolecular palladium‐catalyzed [3+2] formal cycloadditions with imines, offering a straightforward approach to constructing a diverse array of pyrrolidine scaffolds. The best results for the intermolecular variants are obtained using electron deficient imine partners, while the use of oxime ethers proved to be key for the intramolecular cases, which produce bicyclic pyrrolidine scaffolds. We also report preliminary results on enantioselective variants using palladium complexes bearing chiral phosphoramidite ligands. Finally, a DFT analysis provides relevant mechanistic insights, suggesting that the reactions proceed via pallada‐ene type of processes between initially generated palladacyclobutane and the C=N double bond of the imine partner.